2014
DOI: 10.1096/fj.14-251074
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4 + HLA‐G + regulatory T cells are potent suppressors of graft‐versus‐host disease in vivo

Abstract: CD4(+) T cells expressing the immunotolerizing molecule HLA-G have been described as a unique human thymus-derived regulatory T (tTreg) cell subset involved in immunoregulation and parenchymal homeostasis during infectious and autoimmune inflammation. We compared properties and molecular characteristics of human CD4(+)HLA-G(+) with those of CD4(+)CD25(+)FoxP3-expressing tTreg cells using in vitro studies of T-cell receptor (TCR) signaling, single-cell electrophysiology, and functional in vivo studies. Both tTr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…10 A) and resemble those recorded from living cells ( Fig. 7A; (Pankratz et al, 2014)). Switching to the pathophysiological pH value of 6.0 decreased the total transmembrane current in the resting (122 pA; Table 1, Fig.…”
Section: Human Cd4 + T Cell Modelsupporting
confidence: 71%
“…10 A) and resemble those recorded from living cells ( Fig. 7A; (Pankratz et al, 2014)). Switching to the pathophysiological pH value of 6.0 decreased the total transmembrane current in the resting (122 pA; Table 1, Fig.…”
Section: Human Cd4 + T Cell Modelsupporting
confidence: 71%
“…Fluorescence was measured with a TECAN infinite M200Pro fluorimeter (Tecan Group Ltd., Männerdorf, Switzerland). Excitation was alternated between 340 and 380 nm, and emission was measured at 509 nm every 3 seconds [36].…”
Section: Camentioning
confidence: 99%
“…Secondly, we found that the percentage of CD4 1 cells and CD8 1 cells expressing HLA-G molecules was significantly higher in SSc patients than in controls. These CD4 1 HLA-G 1 and CD8 1 HLA-G 1 cells, that are different from the naturally occurring CD25 1 forkhead box protein 3 (FoxP3 1 ) T regs , may be involved in the modulation of immune responses in systemic sclerosis, as it has been reported that these HLA-G-expressing lymphocytes exert potent suppressive function and are present in inflamed tissues of patients affected by immune mediated disorders [50,63,64]. Interestingly, HLA-G molecules were detected in epidermal and dermal cells of skin biopsies from approximately 50% of patients with SSc, and HLA-G expression was associated with a lower frequency of cutaneous ulcers, telangiectasias and polyarthralgias [53].…”
Section: Discussionmentioning
confidence: 99%